(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
A 22 year old man died on the spot in a road accident due to laceration injury over his neck. He was brushed by a passing car from behind while traveling on a bicycle. The deceased lost the control his bicycle and fell over the exposed metallic right end of the rotating handlebar of bicycle. He sustained a horizontally placed laceration injury over the front and both sides of the middle third of neck. Though the pediatric blunt abdominal trauma secondary to bicycle handlebar is widely reported but a fatal neck injury in an adult of this nature is certainly extraordinary and deserves mentioning in the forensic literature.